First language acquisition and steps of learning mother tongue - Olimova, Nodira (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
First language acquisition refers to the way children learn their native language. Second language acquisition refers to the learning of another language or languages besides the native language. It happened spontaneously o children while their parents are talking. Children learn mother tongue by hearing and because of this they can grasp mother tongue. They may listen only this language during the day. The phase of learning first language looks really simple however, it has also different kind of stages that can be learn